Eosinophilic esophagitis: not rare, simply under-biopsied-experience from a tertiary centre in South India - Rishabh Agarwal; Prashant Y. Kanni; Sujatha Udupa (International Journal of Advances in Medicine, 2026)
Eosinophilic esophagitis (EoE) is considered rare in India, yet this perception likely reflects diagnostic omission rather than true epidemiological rarity. We report two cases of EoE diagnosed within a two-month period at a tertiary gastroenterology centre in Bengaluru, South India, from among ten consecutive patients in whom targeted esophageal biopsies were obtained on clinical suspicion-a diagnostic yield of 20%. The first patient was a 54-year-old woman with longstanding proton pump inhibitor refractory dysphagia, chest pain, and regurgitation, whose prior endoscopy had attributed findings to reflux disease without esophageal biopsy. Repeat evaluation revealed mucosal rings with exudates and a peak intraepithelial eosinophil count of 25 per high-power field. She responded completely to vonoprazan and swallowed budesonide. The second was a 37-year-old man presenting with progressive dysphagia and weight loss, with an endoscopic reference score of 7 and a peak eosinophil count of 30-35 per high-power field, who improved on a six-food elimination diet. These cases highlight that co-existent erosive esophagitis may mask EoE endoscopically, and that a protocol-driven biopsy approach is essential to unmask its true prevalence in India.